2013
DOI: 10.3341/kjo.2013.27.5.368
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus in Retinoblastoma Tissues from Korean Patients

Abstract: PurposeRecent reports suggest the association of human papilloma virus (HPV) with retinoblastoma. This study was performed to elucidate whether HPV infection is related to retinoblastoma among Koreans.MethodsA total of 54 cases diagnosed with retinoblastoma were enrolled from Seoul National University Children's Hospital and Seoul Metropolitan Government-Seoul National University Boramae Medical Center. Presence of human papilloma viral DNA was detected by in situ hybridization in formalin-fixed paraffin-embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…The PCR products (360 nucleotide long) of the seven afflicted children with Retinoblastoma (P1, 5,7,9,12,15,20) and their relatives as Controls (C2-C22) are shown in figure 1A. All 22 samples yielded sufficient quality bands (sample # 19 did not show a PCR product in this gel picture but gave a clear band in another run.…”
Section: Pcr Products Of Exon 18mentioning
confidence: 98%
See 1 more Smart Citation
“…The PCR products (360 nucleotide long) of the seven afflicted children with Retinoblastoma (P1, 5,7,9,12,15,20) and their relatives as Controls (C2-C22) are shown in figure 1A. All 22 samples yielded sufficient quality bands (sample # 19 did not show a PCR product in this gel picture but gave a clear band in another run.…”
Section: Pcr Products Of Exon 18mentioning
confidence: 98%
“…Retinoblastoma (RB) is a rare embryonic neoplasm of retinal origin and the most common intraocular tumour in children, with 3% incidence of all paediatric tumours and a frequency averaging 1:20.000 live born in different populations (1)(2)(3)(4)(5)(6)(7)(8)(9). It has good prognosis if diagnosed early but it is lifethreatening when diagnosed late (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Retinoblastoma is an intraocular tumor involving neuroectodermal cells of the retina, affecting 18,000-30,000 children per year (Antoneli et al, 2011; Chauhan et al, 2020; Orjuela et al, 2000; Palazzi et al, 2003; Ryoo et al, 2013; Sachdeva and O’Brien, 2012). Most retinoblastomas arise from inherited or acquired mutations in the RB1 gene, leading to biallelic inactivation of this gene (Friend et al, 1986; Knudson, 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Although this relationship is not always suggested (Palazzi et al, 2003; Ryoo et al, 2013), child exposure to HPV during pregnancy and/or childbirth, indicates vertical viral transmission. In this scenario, it is suggested that HPV could be a factor in the development of oncogenic processes, supporting the idea that the virus is related, in fact, with the etiopathogenesis of RB (Bhuvaneswari et al, 2012; Lee et al, 2013; Skoczyński et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[30] We know high risk HPV's (primarily 16 and 18) are definitely involved in cervical, pharyngeal, penile, anal, vaginal, and vulva cancers [31] and recently meta-analysis suggests HPV is probably involved in other cancers as well such as lung, [32,33] prostate, [34,35] breast, [36] colon, [37] ovarian, [38] bladder, [39] and non-melanoma skin cancer. [40] In addition, HPV has been found in cancers like cutaneous malignant melanoma, [41,42] eye, [43] esophageal, [44] and stomach. [45,46] HPV may be the reason some cancers are recently increasing over time like pancreas, liver, thyroid, and kidney, [47] and is possibly involved in other cancers that have not yet been discovered.…”
Section: Introductionmentioning
confidence: 99%